A robust polyfunctional Pd(II)-based magnetic amphiphilic nanocatalyst for the Suzuki–Miyaura coupling reaction - Hamideh Aghahosseini (Nature Portfolio, 2021)
Abstract Herein, a robust Pd(II)-based polyfunctional magnetic amphiphilic artificial metalloenzyme was prepared by anchoring a Pd(2,2′-dipyridylamine)Cl2 bearing hydrophilic monomethyl ether poly(ethylene glycol) (mPEG) chains on the surface of amino-functionalized silica-coated magnetic nanoparticles. The 2,2′-dipyridylamine (dpa) has shown excellent complexation properties for Pd(II) and it could be easily anchored onto functionalized magnetic support by the bridging nitrogen atom. Moreover, the bridging nitrogen atom at the proximity of Pd(II) catalytic center could play an important role in dynamic suppramolecular interactions with substrates. The leaching, air and moisture resistant [Pd(dpa)Cl2] complex endow the dynamic and robust structure to the designed artificial enzyme. Moreover, the water dispersibility of designed artificial metalloenzyme raised from mPEG chains and the magnetic nanoparticles core which could function as protein mimics endow it other necessary characters of artificial enzymes. The prepared artificial metalloenzyme displayed remarkable activity in Suzuki–Miyaura cross-coupling reaction employing low-palladium loading under mild conditions, with the exceptionally high turnover frequency, clean reaction profile, easy work-up procedure, good to excellent products yields and short reaction times. The designed air- and moisture-stable artificial metalloenzyme could recycle more than fifteen times with easy separation procedure in aqueous solution under aerobic conditions without any noticeable loss in activity.